2019
DOI: 10.1038/s41409-019-0573-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow harvesting from paediatric patients undergoing haematopoietic stem cell gene therapy

Abstract: Collection of an adequate amount of autologous hematopoietic stem progenitor cells (HSPC) is required for ex vivo manipulation and successful engraftment for certain inherited disorders. Fifty-seven paediatric patients (age 0.5-11.4 years) underwent a bone marrow harvest for the purpose of HSPC gene therapy (GT), including adenosine deaminase severe combined immunodeficiency (ADA-SCID), Wiskott Aldrich syndrome (WAS) and metachromatic leukodystrophy (MLD) patients. Total nucleated cells and percentage and abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…However, in their cohort, donor weight positively correlated with marrow harvest TNC cell density, contrary to our findings. In a study evaluating marrow harvest characteristics from children undergoing autologous marrow collections in preparation for gene therapy, Tucci et al reported similar findings to our cohort, with final graft CD34+ cell count correlating inversely with weight and age, 13 the latter of which was also seen in a report of the effect of G‐CSF priming on marrow cell counts 11 …”
Section: Discussionsupporting
confidence: 87%
“…However, in their cohort, donor weight positively correlated with marrow harvest TNC cell density, contrary to our findings. In a study evaluating marrow harvest characteristics from children undergoing autologous marrow collections in preparation for gene therapy, Tucci et al reported similar findings to our cohort, with final graft CD34+ cell count correlating inversely with weight and age, 13 the latter of which was also seen in a report of the effect of G‐CSF priming on marrow cell counts 11 …”
Section: Discussionsupporting
confidence: 87%
“…of harvested HSPCs after mobilization as well as to enhance their "seeding efficiency" after transplantation into hematopoietic BM niches [3].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In subsequent years, two other important sources of HSPCs emerged that are mobilized peripheral blood (PB) and umbilical cord blood (UCB). With all these sources of cells, very often, a number of HSPCs that are present in harvested BM, mobilized PB, or UCB unit are limited [ 1 3 ]. In humans, a successful transplantation requires a sufficient number of harvested HSPCs per kg body weight of the patient, and a fast, consistent, and long-term multilineage engraftment requires the intravenous infusion of a minimum of 2 × 10 6 CD34 + stem cells/kg recipient body weight; however, a higher dose of 5 × 10 6 CD34 + cells/kg is considered preferable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor stem cells are collected directly from the BM space in a procedure called a BM harvest ( 35 ). They may also be collected via peripheral blood after the donor is given a stem cell mobilizing agent to move stem cells into the periphery for collection ( 36 ).…”
Section: Graft Source Typesmentioning
confidence: 99%